Analisis dan Perancangan Sistem Informasi Helpdesk Berbasis Websitepada Perusahaan Swasta Menggunakan Standar ISO/IEC 25010 - Dimas Wahyu Nugroho; Muhammad Malik Saputra; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2026)
PT Teknologi Informatika Solusindo is a company engaged in information technology and digital services. The helpdeskservice process, which is still carried out manually through email and direct communication, causes delayed responses,difficulties in ticket monitoring, and inefficient management of user report data. Therefore, a website-based helpdeskinformation system is needed to support the management of user reports more effectively and in an integrated manner.This study aims to design a website-based helpdesk information system using the Agile method and ISO/IEC 25010standard. The system design was developed using Unified Modeling Language (UML), consisting of use case diagrams,activity diagrams, entity relationship diagrams (ERD), and sequence diagrams. System testing was conducted using theBlack Box Testing method and ISO/IEC 25010 on the aspects of functional suitability, usability, and performanceefficiency.The results show that the developed website-based helpdesk information system is able to make the ticketmanagement process more structured, simplify user report monitoring, and improve the effectiveness of companyservices. Based on the ISO/IEC 25010 testing results, the system has operated according to user requirements andprovides better service quality compared to the previous system